Design and Performance Evaluation of an IoT-Based Automatic Airflow Control System for a PV/T Solar Dryer with Silica Gel Adsorption Heat Storage - Putri Arsyafdini Oktavionry; Leopold Oscar Nelwan; I Dewa Made Subrata (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Solar energy is one of the most promising renewable energy sources, yet solar drying operating costs often remain prohibitive for small-scale farming. This research aims to design and evaluate the performance of an automated air flow control system for a PV/T collector integrated with an adsorption channel. The methodology focuses on developing a real-time monitoring and control logic based on environmental parameters. The system utilizes a microcontroller-based unit for data acquisition of temperature and humidity, coupled with a high-torque motor actuation system to regulate valve positioning between the collector and the desiccant unit. Results indicate that the control system manages air distribution effectively across a temperature control range of 40 °C to 4 3°C. The system demonstrated high responsiveness with a mechanical actuation speed of 3 seconds for a full 90-degree valve rotation. During the adsorption phase, the silica gel's moisture content rose from 23.57% to 27.38%. Furthermore, the silica gel adsorption unit contributed to thermal stability by maintaining a temperature gradient of 3-7 °C between the plenum and the environment, effectively recycling adsorption heat to enhance the drying air temperature even during low solar radiation.